Gestión de talento humano y desempeño laboral en la Municipalidad Provincial de Requena 2024 - Rodriguez Tello, Chiary Thais (2025)
The objective of this research report was to determine the relationship between human talent management and job performance in the Provincial Municipality of Requena, in the year 2024. To do so, a basic descriptive and correlational method was used, using a non-experimental design. The study population consisted of 1,220 administrative workers, to whom a questionnaire was applied to collect the necessary information. It was concluded that human talent management is regular (25%), since, although the municipality occasionally informs about job opportunities and always provides adequate induction and generally respects the payment schedule, it significantly lacks mentoring programs, recognition of achievements and constructive feedback for employees. Regarding job performance, it is considered regular (25%). This is because, although it almost always has the resources to achieve the POI goals, it rarely achieves its goals on time and the work environment is not pleasant. Finally, a correlation coefficient of 0.759 and a significance of 0.000 were determined, it can be concluded that there is a positive and statistically significant relationship between human talent management and job performance.